Household Heads Characteristics and Access to Water in Kenya - Omondi, Beatrice Anyango; Jackson, Mdoe Idi (European Scientific Journal, ESJ, 2022)
Kenya has taken numerous steps in ensuring universal access to water among all households by 2030. However, the country may not achieve this by 2030 due to challenges related to the implementation of objectives including inadequate data on the indicators to allow for better policy formulation. The study aimed at finding out the effect of household head characteristics on access to water. The study employed multinomial logistic regression modeling using 2015/2016 Kenya Integrated Household Budget Survey data. Arising from the study findings, an increase in the income of the household head led to an increase in the household’s access to clean water. Education levels (primary, secondary, and tertiary) of household heads compared to no education increased the probability of household heads selecting clean water sources. Being employed as well as being male increased the probability of accessing clean water. Further, residing in a rural area by a household head reduced the probability of using clean water compared to residing in an urban area. Based on the findings, the study suggests that there is a need to develop a policy around the key and significant household head characteristics to improve access to clean water in Kenya.